Peran Promosi Penjualan dalam Modifikasi Implementasi Technology Acceptance Model (TAM) Pada Niat Menggunakan E-wallet di Denpasar - Oktora Panasea, I Gede Nandya; Erliani, Ni Kadek (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
Electronic payments are a payment method that populer in Indonesia. One of the popular electronic payment methos is e-wallet. The development of e-wallet is supported by the increasing of e-wallet service providers and the increasing growth of merchants that serving payment with e-wallet. The aim of this research are to find out the effect of promotion, perceived ease of use, perceived usefullness on consumer’s attitude toward using and customer’s behavioural intention to use on e-wallet. The reseach was conducted with 300 respondends from different ranges of age in Denpasar City. The data is analyzed by PLS- based SEM. The result showed that promotion, perceived ease of use, and  perceived usefullness had a positive and significant effect on consumer’s attitude toward using and consumer’s behavioural intentionto use e-wallet in Denpasar.